EDP Audit Symposium 1978 Proceedings. - Lemon, W. Morley; Burns, Thomas J. (The Accounting Review, 1980)
The article reviews the book "EDP Audit Symposium 1978 Proceedings," edited by Joseph L. Sardinas, Jr.